2019
DOI: 10.1002/jwmg.21641
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and ecological associations of small mammals

Abstract: Effective conservation and management of small mammals require knowledge of the population dynamics of co-occurring species. We estimated the abundances, autocorrelations, and spatiotemporal associations of 4 small-mammal species from 2011-2016 using live-trapping mark-recapture methods on 9 sites across elevation and canopy openness gradients of a late-successional forest in the H. J. Andrews Experimental Forest, on the west slope of the Oregon Cascades. We also quantified species-specific spatial variation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 87 publications
(115 reference statements)
2
17
1
Order By: Relevance
“…Similarly, capture probability was substantially higher on HJA sites relative to SIU sites. The abundance estimates presented here are similar to those reported by Weldy et al (2019) which were obtained using HJA data. Apparent annual survival was similar on both the HJA and SIU sites.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similarly, capture probability was substantially higher on HJA sites relative to SIU sites. The abundance estimates presented here are similar to those reported by Weldy et al (2019) which were obtained using HJA data. Apparent annual survival was similar on both the HJA and SIU sites.…”
Section: Discussionsupporting
confidence: 89%
“…However, we are unaware of any studies that examined how increasing or decreasing the number of trap nights influences flying squirrel abundance estimates. Weldy et al (2019) recently estimated Humboldt’s flying squirrel abundance using Huggins closed-population models and found the estimates of precision were very small, in some cases small enough that the reported estimates resemble a full census, suggesting that reducing trap nights could be considered. Similarly, considerable time and energy goes into hanging traps on trees.…”
Section: Introductionmentioning
confidence: 99%
“…We felt that this assumption was met on our study-sites, which were randomly placed within a large, continuous, old late-successional forest where site edges did not reflect biological edges. Further, Carey (1995) suggested that there was no evidence that the densities of flying squirrels and chipmunks were misleading indicators of habitat suitability, and Weldy et al (2019) found no evidence for marginal or sink habitat on our study sites. Presence of sink habitats would have indicated that individuals were more likely to emigrate from or immigrate to specific sites.…”
Section: Discussionmentioning
confidence: 62%
“…Flying squirrels have been characterized as a potentially K-selected species, with survival that is higher than similar-sized mammals (Smith, 2007; Villa et al, 1999) and varies little across time (Lehmkuhl et al, 2006). However, other demographic characteristics such as abundance (Weldy et al 2019), sex ratio (Rosenberg & Anthony, 1992), and recruitment (Weldy et al 2020) vary substantially across time. Much less is known about chipmunk demography, but they have been characterized as an r-selected species with population growth rates primarily driven by recruitment and generally lower survival which can exhibit substantial temporal variation (Weldy et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…
Small terrestrial mammals are of extraordinary importance in most terrestrial ecosystems (Barrett and Peles, 1999;Weldy et al, 2019). Their biomass, relatively high and variable abundance, short generation interval, and rapid response to changing conditions make them one of the most sensitive bioindicators of change throughout the environment (e.g., Pearce and Venier, 2005;Heroldová et al, 2018).
…”
mentioning
confidence: 99%